Personal characteristics and showing love in marriage: unmitigated communion, psychological entitlement and need for affect - Kamenov, Željka (Array, 2012)
Personality traits, as specific characteristics that help individuals regulate behavior, can help explain differences in relationship behavior. In this study we examined the role unmitigated communion (excessive focus on others and their needs), psychological entitlement (a sense of being more deserving than others), and need for affect (motivation to approach/avoid emotion-inducing situations) play in showing love to one's married partner. We hypothesized that individuals with higher unmitigated communion and higher need for affect will show love in more specific ways, while the reverse was expected for psychological entitlement. We tested 302 Croatian and 456 Serbian married couples of different ages (20-82 years) and various urban/rural backgrounds. Length of marriage varied between one month and 57 years. We administered the Revised Unmitigated Communion Scale (Helgesson and Fritz, 1998), the Psychological Entitlement Scale (Campbell et al., 2004), the short version of Need for Affect Scale (Maio and Esses, 2001 ; shortened by Huic, 2010), and the Ways of Showing Love Scale (constructed for this study). In general, both men and women with higher unmitigated communion report they show more love, but their partners' perceptions generally do not correspond to this. The only exception are Croatian husbands with higher unmitigated communion whose wives perceive that they show more love to them. Men and women with higher need for affect expectedly report on showing more love, they see their partners showing more love to them, and their partners perceptions correspond with their self-reports. Not in line with our expectations, psychological entitlement does not seem to effect displays of love in marriage. Some specific patterns of results with regard to different ways of showing love dimensions and some interesting cultural differences are elaborated.